Guillain-Barré syndrome after varicella-zoster virus infection - Inan, Yasemin; Degerliyurt, Aydan; Uysal, Hilmi; Keyik, Bahri; Uysal, Gulnar (Journal of Pediatric Neurology, 2007)
Guillain-Barré syndrome (GBS) is an acute inflammatory, demyelinating polyradiculoneuropathy. The neurological complications of varicella-zoster virus (VZV) infection are usually cerebellar ataxia and other forms of encephalitis. VZV is associated with only 1% of the GBS cases. GBS may present as a clinical picture mimicking encephalitis. We report a patient with GBS who presented with altered consciousness and flaccid paralysis of the legs, three weeks after VZV infection.
Keywords: Guillain-Barré syndrome; encephalitis; child